Efficacy of dinotefuran 20 SG against brown planthopper (Nilaparvata lugens Stål) in basmati rice - Jaglan, Maha Singh; Chaudhary, Om Pal (Journal of Cereal Research, 2022)
Brown planthopper, Nilaparvata lugens Stål is a dominant species among the noxious rice pests and causes considerable damage in India. Various strategies have been employed to manage brown planthopper and insecticides factor as the frontline defense. However, it has now become difficult to manage brown planthopper with the present genre' of insecticides due to the development of resistance. Identification of new molecules with selective properties, a novel mode of action, low toxicity to non-targets and environmental safety becomes a newer tool for the sustainable management of brown planthopper. In this direction, dinotefuran 20 SG a new molecule was evaluated under field conditions to access its efficacy against brown planthopper in basmati rice during Kharif, 2019.